A Way to Know, A Way to Go (Revista Apotheke, 2017)
Barbara Ellmann, a New York painter and freelance teaching artist, describes an innovative concept that combines her work as a fine artist and as an aesthetic educator into an exhibition's unusual design. She discusses the experiences that led to her exhibition and the ideas that have developed over thirty-five years of painting and teaching. As an educator at The Museum of Modern Art and The Whitney Museum and having observed the distance between curatorial decisions and the location of educational experiences she questions how else art could be presented to the general public and to student groups. AN OPEN BOOK, work by Barbara Ellmann is an attempt to break the wall-text conventions of explanatory and didactic language by providing instead visual support materials for visitors to explore in the exhibition itself. On reflection both obvious and a surprise to her was the discovery that a lifetime of work as an artist had led to the innovations visible in this exhibition.